PEMANFAATAN LIMBAH KOTORAN HEWAN PADA CAMPURAN BETON DI TINJAU DARI KUAT TEKAN - Subaidillah Fansuri; Dwi Deshariyanto; Nor Zainah (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2026)
Indonesia has a lot of animal waste; this animal waste causes air pollution and becomes a center for the spread of disease. Because cow dung has a silica content of 9.6% per kilogram, silica is the main ingredient in cement, so the study uses cow dung as an additional ingredient in making concrete which will be reviewed from the compressive strength with the proportion of cow dung additives of 0%, 5%, 10% and 15%. This study conducted a normal concrete experiment with a concrete quality of 20 Mpa which was given additional cow dung waste with variations of 0%, 5%, 10% and 15%. Using a cube-shaped test object measuring 15 x 15 x15 at the age of 5 days and will be tested using test objects, testing test objects such as slump testing, and compressive strength to obtain the quality of concrete from the research sample. This study was conducted to produce quality and economical concrete while preventing pollution caused by animal waste by utilizing the waste as an additional ingredient in concrete making. This study used cow dung ash as an additional material of 0%, 5%, 10%, and 15%. The results of this study obtained an average compressive strength of 14.592 MPa for the 0% variation, 14.370 MPa for the 5% variation, 10.22 MPa for the 10% variation, and 9.407 MPa for the 15% variation.